(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Translanguaging refers to the practice of using multiple languages in a flexible, dynamic way to make meaning and facilitate communication. The idea that in foreign language classes the use of L1 can be beneficial for students is gaining ground in foreign language teaching methodology. Translanguaging is a relatively newly coined term that is often used to refer both to the process of switching between two languages and the methodology that lies behind it. After presenting the main characteristics of translanguaging and the possibility of implementing it as a pedagogical method in English language classrooms, the paper presents a translanguaging activity and also shows how the students evaluated their participation in this practice. The paper concludes that in order to employ translanguaging practices in the classroom, it is necessary to adopt a new mindset to teaching that allows for multiple language use in class and also encourages language learners to embrace their entire linguistic potential.